Experiences and mentoring needs of novice nurse educators at a public nursing college in the Eastern Cape - Khanyisa Sodidi; Sihaam Jardien-Baboo (AOSIS, 2020)
Background: When novice nurse educators enter academia, they are expected to demonstrate and implement knowledge in the clinical and classroom environment. However, when one enters academia without proper guidance and support, these expectations create lack of role models. Although mentorship has proved to make the transition easier, there is a lack of mentoring in most nursing schools and/or departments at higher education institutions in South Africa because of scarcity of mentoring programmes for novice nurse educators. Aim: The aim of this study was to explore and describe the experiences and mentoring needs of novice (newly qualified) nurse educators at a public nursing college in the Eastern Cape, to make recommendations for the mentoring of novice nurse educators. Setting: Urban and rural public nursing college campuses and sub-campuses in the Eastern Cape. Methods: Qualitative research approach and exploratory, descriptive, contextual and phenomenological designs were used. Sampling was purposive, data were collected by using semi-structured individual interviews and analysed using Tesch's method. Results: Five themes emerged from this study. Findings indicated that novice nurse educators experienced lack of theoretical and clinical mentoring and lack of orientation and resources. Participants also provided recommendations to optimise the experience and performance of novice nurse educators. Conclusion: Lack of mentoring causes difficult transition by novice nurse educators from the nursing role into the nurse educator role. The implementation of the recommendations on mentoring of novice nurse educators would optimise the experience and performance of the novice nurse educators, thus enhance their smooth transition into academia.